Public Space and Public Protest in Kuwait - Al-Nakib, Farah (2014)
Events across the globe in 2011, from the Occupy movements to the Arab uprisings, have made salient Henri Lefebvre's assertion that ‘the city and the urban sphere are … the setting of struggle; they are also, however, the stakes of that struggle’ (Lefebvre, H. 1991. The Production of Space. Oxford: Blackwell, 386). This paper analyzes the city as both the site and stake of political contestation between state and society in Kuwait, and the relationship between contentious politics and city formation after the advent of oil. Specifically, it traces the spatiality of public protest from the 1930s until today alongside the changing social composition of opposition forces. During each new period of contestation, both the government and opposition adopted new spatial tactics that left their mark on the urban landscape. The paper focuses on the role of particular public spaces like the historic Sahat al-Safat and the newer Sahat al-Irada, and semi-private spaces like diwāwīn and civil society organizations, in giving form to the discursive public sphere.